Evaluation of the Implementation of Mangrove Thematic Environmental Education in Indramayu, West Java. Issue 1 (1st November 2022) - Rosviani, L; Kusmana, C; Rachmawati, E; Gunawan, H
Abstract: Mangroves are one of the natural habitats that we must preserve. One of the damage to mangrove forests is caused by the lack of knowledge and awareness of the community. Efforts to preserve through this knowledge and awareness can be given to the next generation from an early age. One of the conservation efforts is the existence of mangrove thematic environmental education spread from the west to the east of Indramayu. This study aim to identify the general conditions of each mangrove school and to evaluate the implementation of Mangrove Thematic Environment Education from students knowledge, attitudes, and behaviors. The analysis to be assessed is the influence of learning on knowledge, attitudes, behavior, and the influence of infrastructure on student attitudes and behavior. T-values Results Calculate learning variables with knowledge (10, 707), attitudes (6, 072), and behavior (3, 338). While the test results for aspects of facilities and infrastructure did not have a significant influence on student attitudes and behavior. The facilities and infrastructure contained in the school have not fully supported the activities of students to study mangroves. Evaluation related to mangrove Thematic Living Environment Education, namely the need to improve learning methods and facilities externally so that students are more familiar with mangroves.